Designing a PPDB System Using the Rational Unified Process (RUP) Method: Case Study at: Pakenjeng ICT High School - Ai Rahayu; Demi Dharma Bakti; Dian Rahadian (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
New Student Admissions (PPDB) is a crucial process in educational administration that requires a structured, user-friendly, and secure system. Digitizing web-based PPDB is necessary to improve the efficiency of school administration and minimize errors in processing prospective student data. This research aims to design a web-based PPDB information system at the Pakenjeng Islamic Education (ICT) Center using the Rational Unified Process (RUP) method. The scope of the research is limited to the system design stage, specifically the Inception and Elaboration stages, without system implementation and testing. The main outputs of this research are a system requirements specification document (functional and non-functional requirements), a system architecture design, and system modeling using the Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The main contribution of this research lies in the design of a PPDB system integrated with a system-based selection mechanism and a data security design using the Playfair Cipher cryptographic algorithm to protect prospective students' personal data. It is hoped that the results of this design can serve as a reference and foundation for developing a web-based PPDB system that is safer, more structured, and more efficient in the next implementation stage.